The Insurance Operations and their impact of improving the performance of the Iraqi General Insurance Company : Applied research (Journal of Accounting and Financial Studies ( JAFS ), 2025)
The research aims to identify the impact of insurance operations represented by (fire insurance, car insurance, engineering insurance, marine insurance, life insurance) in improving the performance of the Iraqi General Insurance Company as a place of application. The research problem was identified by identifying the impact of the insurance operations practiced by the researched company on improving its performance level. The descriptive analytical approach was relied upon, and accordingly, the financial statements, annual reports, and statistics of the researched company and the annual reports issued by the Federal Financial Supervision Bureau for the years (2018-2022) were relied upon to analyze them and interpret the extracted results. The research reached a set of results, including: The existence of an impact of the insurance operations practiced by the company on improving its performance.